Caffeic acid phenethyl ester protects kidneys against carbon tetrachloride toxicity in rats - Ogeturk, M; Kus, I; Colakoglu, N; Zararsiz, I; Ilhan, N; Sarsilmaz, M (Elsevier Ireland Ltd, 2005)
Caffeic acid phenethyl ester (CAPE), an active component of propolis produced by honeybees, exhibits antioxidant and anti-inflammatory properties. The aim of this study was to investigate possible protective effects of CAPE on carbon tetrachloride (CCl4)-induced renal damage in rats. A total of 24 animals were divided into three equal groups: the control rats received pure olive oil Subcutaneously, rats in the second group were injected with CCl4 (0.5 ml/kg, s.c. in olive oil) and rats in the third group were injected with CCl4 (0.5 ml/kg) plus CAPE (10 mumol/kg i.p.) every other day for one month. At the end of the experimental period, the animals were sacrificed and blood samples were collected. Serum urea and creatinine levels and renal malondialdehyde (MDA) contents were determined. Histopathological examination of the kidney was also performed using light microscopic methods. It was found that kidney MDA levels were increased significantly following CCl4 exposure and this increase was significantly inhibited by CAPE treatment, while no significant changes were observed in serum urea and creatinine levels. CCl4 administration alone also caused histopathologically prominent damage in the kidney compared to the control group. Glomerular and tubular degeneration, interstitial mononuclear cell infiltration and fibrosis, and vascular congestion in the peritubular blood vessels were observed in the renal cortex. With exception of rare vascular congestions, these histopathological changes were disappeared in rats treated with CCl4 plus CAPE. In view of the present findings, it is suggested that CAPE protects kidneys against CCl4 toxicity. (C) 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: caffeic acid phenethyl ester; carbon tetrachloride; nephrotoxicity; histopathology; light microscopy